Precision control of polyurethane filament drafting and winding based on machine vision - Wu, Shilin; Yang, Huayu; Liu, Xiangyan; Jia, Rui (Frontiers in Bioengineering and Biotechnology, 2022)
In the biomedical field, polyurethane (PU) is widely used in interventional catheters, artificial hearts, artificial blood vessels, orthopedic materials, medical adhesives, and other medical devices. In this paper, a method based on machine vision was proposed to control the drafting and winding accuracy of PU filament in order to solve the problem of centrifugal runout when the mold rotates, which directly affected the preparation efficiency and quality of long artificial blood vessel by wet spinning. Through non-contact real-time detection of the filament diameter and the angle between the axis of filament and the axis of mold, the motion parameters of the two motors driving the moving platform and the drafting roller could be adjusted in real time to achieve the purpose of online real-time control of filament drafting and winding accuracy. The vision control method proposed in this paper was used to carry out the PU tube preparation experiment. The visual measurement results of the filament diameter and the included angle were compared with the manual measurement results. The average value of the diameter error is 0.0096mm, and the average value of winding angle is 0.4777°. The results proved the accuracy of the visual measuring method and testified it feasible to using machine vision instead of manual method to detect filament diameter and winding angle. Properties of the prepared PU tube were tested and analyzed. The filament diameter measured by the 3D microscope was about 0.87mm and significantly smaller than the filament diameter before winding. This indicated that the winding was uniform, the extrusion was tight, and the adhesion was good.